"Plurethosome" as Vesicular System for Cutaneous Administration of Mangiferin: Formulative Study and 3D Skin Tissue Evaluation - Maddalena Sguizzato; Francesca Ferrara; Paolo Mariani; Alessia Pepe; Rita Cortesi; Nicolas Huang; Fanny Simelière; Paola Boldrini; Anna Baldisserotto; Giuseppe Valacchi; Elisabetta Esposito (MDPI AG, 2021)
Human skin is dramatically exposed to toxic pollutants such as ozone. To counteract the skin disorders induced by the air pollution, natural antioxidants such as mangiferin could be employed. A formulative study for the development of vesicular systems for mangiferin based on phosphatidylcholine and the block copolymer pluronic is described. Plurethosomes were designed for mangiferin transdermal administration and compared to ethosome and transethosome. Particularly, the effect of vesicle composition was investigated on size distribution, inner and outer morphology by photon correlation spectroscopy, small angle X-ray diffraction, and transmission electron microscopy. The potential of selected formulations as vehicles for mangiferin was studied, evaluating encapsulation efficiency and in vitro diffusion parameters by Franz cells. The mangiferin antioxidant capacity was verified by the 2,2-diphenyl-1-picrylhydrazyl assay. Vesicle size spanned between 200 and 550 nm, being influenced by phosphatidylcholine concentration and by the presence of polysorbate or pluronic. The vesicle supramolecular structure was multilamellar in the case of ethosome or plurethosome and unilamellar in the case of transethosome. A linear diffusion of mangiferin in the case of ethosome and transethosomes and a biphasic profile in the case of plurethosomes indicated the capability of multilamellar vesicles to retain the drug more efficaciously than the unilamellar ones. The antioxidant and anti-inflammatory potential effect of mangiferin against pollutants was evaluated on 3D human skin models exposed to O3. The protective effect exerted by plurethosomes and transethosomes suggests their possible application to enhance the cutaneous antioxidant defense status.